Imprensa privada e Estado numa sociedade orientalizada : Uma visão crítica sobre Cabo Verde no início do século XXI - Medina, João Almeida (2007)
This work studies the political power relations between the private press, particularly the newspapers A Semana and Expresso das Ilhas, other organizations of the culture and the politic society in Cape Verde. The gramscian concept of State is considered basic, while relationary field of permanent fight, of influences and against-influences, to characterize the archipelago as orientalized society, not in the geographic direction. But its tried to evidence the multiple fragilities of the incipient civil society of the country in the negocial process with the politics, in which the intellectuals find a litlle space to develop its activities with a minimum of autonomy, the citizens almost always stay in silence when the main chacacter is the life politics and the press shows more as an agent moderator of the restricted debate between the two blocks that dispute the power and the collective entities. Its argued that the capeverdian media privilege the institucional sources in detriment of the atomized citizen. Based in this idea, the studie discuss the (in) dependences politics, economic or ideological of this journals, and rediscussed the concepts of journalistic objectivity and impartiality as well as the idea of social responsibility in the political capeverdian conjuncture. Its fomented that nor the periodicals constitute supreme entities, supply-historical, capable to exert a social control omnipresent, nor the public shows shrewd enough to create resistance mechanisms that stop any attempt of manipulation of the sources or of the agents of media. The process is proven complex and to understand it in the capeverdian reality is the challenge of this work